Pengaruh Latihan Senam Kegel Terhadap Inkontinensia Urine Pada Lansia Di RS Toeloengredjo Pare - Sulistyawati, Aulia Ika; Abdullah, Ahmad; Kasimbara, Rachma Putri; Fau, Yohanes Deo (Jurnal Keperawatan Muhammadiyah, 2022)
Objective Â The purpose of this study was to determine the effect of Kegel exercises on urinary frequency in elderly patients at the Geriatrics Polyclinic, Toeloengredjo Hospital.Methods: This article Â This type of research was conducted using the "One Group Pretest and Posttest" design because there was only one group that was taken as the research subject. In this study, a group of 23 research subjects were given Kegel exercises 2 times a week for 4 weeks. This study measures the evaluation results of the QUID score which is used as a measuring tool in research before and after being given treatment. The instruments used are writing instruments and a QUID scale assessment sheet with purposive sampling.Results: The study was conducted on 23 elderly populations with the age category of patients between 60->70 years. The sample of the elderly population taken was the elderly who experienced urinary incontinence who came to the Geriatrics Polyclinic, Toeloengredjo Hospital, Kediri City. And this research was conducted in September 2021 by giving Kegel exercise therapy 8 times which showed the results of changes in the QUID score in reducing the frequency of urination as seen from the table of decreasing numbers from pretreatment and posttreatment.Conclusion: Kegel exercise was effective in reducing the frequency of urination in conditions of urinary incontinence.